An alternative Semi-Autotropic Hydroponics (SAH) substrate for cassava rapid propagation: a first study case - Binzunga, M.M.; Kintche, K.; Sikirou, M.; Adetoro, N.; Dieng, I.; Angelique, K.; Mignouna, J.; Nyende, A.B. (2024)
The expansion of Semi-Autotrophic Hydroponics technology to address the issue of multiplying and disseminating virus-free planting materials for vegetatively propagated crops is challenged by the utilization of imported substrate, namely, KlasmannTS3. In this study, we evaluated the growth parameters and cutting production of cassava genotypes during three subsequent plantlet production cycles using three single substrates, namely, KlasmannTS3 (K), vermiculite (V), and local peat (P), and three blended substrates. The blended substrates were a combination of 25% K and 75% P (K25P75), a combination of V and P at respective rates of 25% and 75% (V25P75), and respective rates of 10% and 90% (V10P90). All cuttings obtained in one plantlet production cycle were transplanted into the next. The multiplication rate of cutting from cycle 1 to 2 (R1) and cycle 2 to 3 (R2) was calculated as the ratios of the number of cuttings per the number of plantlets in each cycle. K and K25P75 led to similar R1 and R2, except with the genotype IBA961089A, where K25P75 led to a higher R1. Local peat and V solely showed similar cutting multiplication rates, and were lower than V25P75 and V10P90. Substrates with a higher cutting production also led to a higher plantlet height, leaf, and internode number. V and its combinations with local peat led to the densest plantlet root system. The performance of the substrates contrasted among the genotypes, but IBA961089A mostly outperformed the two other genotypes. We concluded that up to 75% of K and, to a lesser extent 75% of V, can be substituted by P without compromising cutting production. V and P should be combined instead of being used separately.